2000
DOI: 10.1055/s-2000-10545
|View full text |Cite
|
Sign up to set email alerts
|

Veränderungen des Linsenepithels bei Diabetikern und Nichtdiabetikern mit verschiedenen Trübungsformen einer altersassoziierten Katarakt12

Abstract: The significantly lower mean cell density in type-II diabetics compared with nondiabetic eyes and in posterior subcapsular cataracts in comparison with nuclear and cortical cataracts seem together with the other morphological cell characteristics to be due to the cataractogenic influence of diabetic metabolic disorder on the lens epithelium, especially in cases of posterior subcapsular opacity. These may be some clues for the primary cataractogenic importance of the lens epithelium in type-II diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Zaczek and Zetterstrom [ 14 ] reported similar findings at 2 years. A possible explanation for the lower PCO in diabetic patients may be the decreased density of LECs in the diabetic capsular bag [ 15 ] and/or the detrimental effects of accumulating intracellular sorbitol [ 16 ] and fructose, free radicals, and oxidative stress on their survival and proliferative capacities [ 17 ]. These effects may explain the decrease in the incidence of PCO in diabetic patients at longer follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Zaczek and Zetterstrom [ 14 ] reported similar findings at 2 years. A possible explanation for the lower PCO in diabetic patients may be the decreased density of LECs in the diabetic capsular bag [ 15 ] and/or the detrimental effects of accumulating intracellular sorbitol [ 16 ] and fructose, free radicals, and oxidative stress on their survival and proliferative capacities [ 17 ]. These effects may explain the decrease in the incidence of PCO in diabetic patients at longer follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Struck et al sought to investigate this issue in their study of lens epithelial cell densities in type-II diabetics vs. non-diabetics undergoing cataract surgery [22]. They collected capsulotomy specimens from 59 human subjects and analyzed the cell density of the LEC with respect to diabetic status and cataract type.…”
Section: Discussionmentioning
confidence: 99%
“…age-related cataract, the first changes are -according to the absolute morphological criteriadamages of the fibres of the lens [17]. Tests by Struck et al [30,31] showed the first evidences of damage of the lens epithelium within the scope of the cataractous effect of diabetes mellitus type II. Hence, studies of histomorphological and metabolic changes of the clinically clear human lens are of great importance.…”
Section: Introductionmentioning
confidence: 99%